Nursing perspectives on transitional care between paediatric intensive care units and general wards: A focus group study. (12th October 2022) - Ji, Jianlin; Yang, Hanlin; Yang, Liling; Jiang, Yan; Tang, Ping; Lu, Qunfeng
Abstract: Aim: We aim to explore the experiences of nursing staff in paediatric intensive care units (PICUs) and wards when transporting and caring for patients being discharged from PICU. Background: PICU discharge is a challenging and complex procedure with risks and complications for patients. Nursing staff in PICU and paediatric wards play a pivotal role in the transition and are responsible for the quality of care, but their perspectives have rarely been explored. Methods: Focus groups were conducted between December 2021 and January 2022 with purposively sampled PICU nurses and ward nurses. Four focus groups were formed, and data were analysed using qualitative content analysis. Results: The overarching themes were as follows: communication during handover, attitudes towards follow‐up, a challenging transition for nurses and parents and suggestions for optimizing transitional procedure. Conclusion: Our findings provide nurses' insights and knowledge regarding the transition of patients from the PICU to the ward. Nursing strategies including the use of liaison nurses and critical training for ward nurses were considered essential to maintaining competence during transition. A well‐structured handover checklist as well as interdisciplinary cooperation and transitional care units are important for the patient's quality of care. Implication for nursing management: Communication, cooperation, planning and professional care are vital during the transition process. Nurse managers should work to develop collaborative approaches to facilitate safe patient transition.